Lessons from Deborah’ Inspiration and Implications on the Plight of Women Leadership in A Male Dominated Society: Significances for Today’s World - Rugyendo, Medard (Kabale University, 2024)
Though this is a bible-centered article, it partly falls under the 5th of the 17 sustainable development goals namely to achieve gender equality and empower all women and girls. Gender equality is not only a fundamental human right, but a necessary foundation for a peaceful, prosperous, and sustainable world (un.org/sustainable development/sustainable-development- goals). The Jewish culture was a male-dominated society yet women had great roles and contributions in the social, economic, religious, and political fields. The male Jews used to have the morning prayers that included “Blessed are you, LORD our God, Ruler of the Universe, who has not made me a woman.” This view openly expressed a quintessential misogyny that lies at the core of a patriarchal religion.” Other examples included being left out in the counting of those that Jesus fed (Matt.14:21). They couldn’t be counted as the Israelites were leaving Egypt (Ex.12:37). They couldn’t be allowed to speak in the church (1 Cor.14:33b-36). Women couldn’t be placed in higher positions of leadership in the Jewish community yet women like Deborah the prophetess and judge in the Old Testament (Judges 4 & 5) inspired the Israelites who later defeated the Canaanite oppressors. Though Deborah was a heroine and the only woman among the twelve (12) judges of Israel, she was not included in the Hall of Faith in the Book of Hebrews 11. What was the nature of male dominance among the Israelites? Therefore, this is an assessment of a bible-based article but with other extra-biblical sources about the plight and position of women leadership in a male-dominated society based on Deborah. The implications of her achievements will inspire this 21st-century world that experiences gender-based challenges in leadership at various levels.